An Analysis of Nicotine Pouch Use by Middle School and High School Students Surveyed by the National Youth Tobacco Survey in 2021 and a Review of the Literature - Zachary Speciale; Sanjana Rao; Shengping Yang; Kenneth Nugent (SAGE Publishing, 2023)
Objectives: The use of alternative nicotine products by middle and high school students is a growing concern due to industry marketing techniques, availability, and popularity of new products, and ambiguous nicotine concentrations. The 2021 National Youth Tobacco Survey (NYTS) provides information about the frequency, and characteristics of middle, and high school students who have used nicotine pouches. Methods: The National Youth Tobacco Surveys provide important information about the frequency of use of tobacco and alternative nicotine products by a representative sample of students in schools in the United States. The 2021 survey included questions about the use of nicotine pouches/dissolvable tobacco products. The results from the survey were analysis using descriptive statistics, and logistic regression to model the association between the use of these alternative nicotine products, and the use of electronic cigarettes or the use of conventional cigarettes. Results: A total of 20 413 students participated in the survey year 2021; 17 842 were included in the final data analysis. Their ages ranged from 9 to 18+. Identified risk factors for the use of alternative nicotine products included race, and age. The adjusted odds ratio (OR) was lower in non-Hispanic Black and Hispanic students, as compared to non-Hispanic White students. Older students had a substantially higher risk of using nicotine/dissolvable tobacco products, specifically, compared to students less than or equal to 13 years old. The OR increased 174% (OR: 2.74; 1.70-4.41) in 17-year-old students. The perception of harm associated with electronic cigarettes increased the likelihood of using alternative nicotine products. Students who did not smoke cigarettes (OR: 0.39; 0.27-0.56) or did not smoke electronic cigarettes (OR: 0.20; 0.18-0.40) had significantly lower OR for using alternative nicotine products. Conclusions: The 2021 National Youth Tobacco Survey indicates that a relatively small percentage of middle school and high school student have used nicotine pouches. However, with the increase in new, alternative tobacco products, understanding adolescent use in comparison to other tobacco products is an important trend to monitor.